New CARs on and off the road: challenges and new developments in CAR-T cell therapy. (August 2021) - Wehrli, Marc; Maus, Marcela V.
Abstract: Building on the tremendous success of chimeric antigen receptor T-cell therapy in hematological malignancies, there are efforts under way to overcome the challenges associated with this treatment and expand its application to solid tumors. In this fast-evolving field, new therapeutic options are constantly generated, tested in model systems, and further evaluated in clinical trials. In this review, we provide an overview of recent challenges and developments associated with engineered T cells and chimeric antigen receptor T-cell applications. We report on the most recent progress in hematological malignancies and highlight technical advances for applications in solid tumors. Highlights: Attempts are under way to increase safety of chimeric antigen receptor (CAR) T cells in hematological malignancies. There is a large body of work aiming to increase CAR T-cell–mediated tumor selectivity. Solid and hematological malignancies can be treated with CAR T cells targeting multiple antigens. Cell types other than T cells are under investigation for genetically modified immunotherapy applications.